The private shareholder and the corporate report : a report to the Research Committee of the Institute of Chartered Accountants in England and Wales - Lee, T. A.; Tweedie, D. P.; Institute of Chartered Accountants in England and Wales, London (London : Institute of Chartered Accountants in England and Wales, 1977)
This book is concerned with one of the most familiar aspects of accountancy - that of company financial reporting.
Includes bibliographical references p. 176-177.
hza 11/09/2018
Loans
Keywords: Corporation reports